Cointegration and the Demand for Gasoline - B. Bhaskara Rao; Gyaneshwar Rao (Economics and Econometrics Research Institute (EERI), 2008)
Since the early 1970s there has been a worldwide upsurge in the price of energy and in particular of gasoline. Therefore, demand functions for energy and its components like gasoline have received much attention. However, since confidence in the estimated demand functions is important for use in policy and forecasting, following Amarawickrama and Hunt (2008), this paper estimates the demand for gasoline is estimated with 6 alternative time series techniques with data from Fiji. Estimates with these 6 alternative techniques are very close and thus increase our confidence in them. We found that gasoline demand is both price and income inelastic.
Keywords: Q40; Q41; 330; Gasoline Demand; Income and price elasticities; Cointegration